Beta-lactam antibiotics administration among adult inpatients with a beta-lactam allergy label: incidence, predictors, and outcomes - Naama Epstein-Rigbi; Sharon Ziv; Marina Bulanenkova; Ruth Bouganim; Ruthy Tal-Jasper; Dror Marchaim (Cambridge University Press, 2024)
Abstract Background: A beta-lactam antibiotics (BLA) allergy label is common, resulting in disadvantageous outcomes due to the usage of second-line antimicrobial agents. Noncontrolled case-series analyses report low rates of hypersensitivity reactions, following intentional/non-intentional BLA challenges among labeled inpatients. The study aims were to explore predictors and outcomes associated with hypersensitivity reactions following BLA challenge among BLA-allergic labeled inpatients. Methods: Retrospective cohort study (2019-2020) of adult (≥18 years) inpatients (Shamir Medical Center, Israel), labeled as allergic to ≥1 BLA, who received ≥1 dose/s of BLA during their stay. Independent predictors to develop allergic reactions and the independent associations of allergic reactions with clinical outcomes were queried by logistic and Cox regressions. Results: Of 9,670 inpatients (14,088 hospitalizations), 3,570 (37%) were labeled as allergic to ≥1 BLA. Of those, 1,171 (33%) patients received ≥1 BLA. The majority were women (67%), and the mean age was 69.3 ± 19.4 years. Only 30 patients (2.6%) developed a reaction, all mild. Independent predictors to develop an allergic reaction were documented reactions in the past, atopic background, antihistamines administration prior to the BLA challenge, and high risk for cross-reactivity, based on the BLA side chains, between the labeled and the challenged agents. Reaction upon the BLA challenge was not independently associated with any worse outcome. Conclusions: Despite the commonality of allergy labeling, and the commonality of BLA administration to labeled inpatients, hypersensitivity reactions were mild and rare. Interventional stewardship strategies for active BLA de-labeling among low-risk patients should be promoted, to improve patients' and institutional health and fiscal outcomes.